Diaphragm and preparation method and application thereof, lithium ion battery

By using slurry blended with low-density polymer microspheres and inorganic powder in lithium-ion battery separators to perform secondary polymerization reactions, the existing separators have poor anti-swelling ability and complex preparation methods have been solved, and a separator with high adhesion and swelling resistance has been achieved, extending the battery service life.

CN119581789BActive Publication Date: 2025-04-29ANHUI ESTONE MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510138047.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-29
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have poor anti-swelling ability during circulating charging and discharging, resulting in a decrease in adhesion and affecting the battery life. The preparation method is complicated and additional adhesive is required. Small-particle size products are not conducive to improving the injection speed.

Method used

Low-density polymer microspheres are blended with inorganic powder to form a slurry, and a secondary polymerization reaction is carried out in the redox initiation system to form a separator with high adhesion and swelling resistance.

Benefits of technology

The adhesive force between the separator and the electrode sheet is improved, the electrolyte resistance and swelling resistance are enhanced, the battery life is extended, and the preparation method is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581789B_ABST
    Figure CN119581789B_ABST
Patent Text Reader

Abstract

The invention discloses a diaphragm and a preparation method and application thereof, and a lithium ion battery, and relates to the technical field of lithium ion batteries. The invention prepares incompletely polymerized low-density polymer microspheres as a binder, and uses a slurry containing the low-density polymer microspheres for base film coating. Under the action of buoyancy, the low-density polymer microspheres rise to the surface of the slurry and form a convex structure on the surface of the slurry. The convex structure can more effectively bond the diaphragm and the pole piece, that is, improve the bonding force between the diaphragm and the pole piece; in addition, the low-density polymer microspheres can make the prepared diaphragm have good electrolyte tolerance and anti-swelling properties through a secondary polymerization reaction, so as to exert a long-lasting bonding effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a diaphragm and a preparation method and application thereof, and a lithium ion battery. Background Art

[0002] In recent years, in order to achieve sustainable development and protect the ecological environment, lithium-ion battery technology has been widely used. Electric vehicles equipped with lithium-ion power batteries are becoming increasingly popular. At the same time, lithium-ion batteries are also widely used in 3C, energy storage and other fields. These data show that lithium-ion batteries will play an increasingly important role in the next decade or even longer. In the field of lithium batteries, polyvinylidene fluoride (PVDF) has always occupied an important position due to its excellent chemical stability, thermal stability, electrical insulation and good mechanical properties. PVDF is not only the preferred material for lithium battery positive electrode binder, which can firmly bond active substances and conductive agents to aluminum foil, but also plays a key role as a coating layer in battery separators. However, with the rapid development of the global new energy vehicle industry and the rapid rise of the energy storage market, the demand for lithium batteries has exploded, and PVDF is also facing unprecedented challenges.

[0003] However, with the rapid development of the global new energy vehicle industry and the rapid rise of the energy storage market, the demand for lithium batteries has exploded, and PVDF is also facing unprecedented challenges. The supply of R142b, a key raw material for the production of PVDF, is also strictly restricted. As a HCFC refrigerant, R142b has been gradually phased out by developed countries due to its destructive effect on the ozone layer. Domestic production has also been subject to a quota system since 2013. Against the backdrop of many difficulties facing PVDF, polymethyl methacrylate (PMMA) microspheres have gradually emerged as a potential alternative and have been partially used in the field of lithium battery separator coating. PMMA microspheres are a type of high molecular polymer microsphere with good chemical stability, thermal stability and compatibility with electrolytes.

[0004] CN 103250273A discloses a secondary battery porous membrane, which is manufactured using a secondary battery porous membrane slurry with excellent coating properties and non-conductive organic particles. This invention also provides non-conductive organic particles with low metal impurity content and suitable for secondary battery porous membranes. This patent uses a seed polymerization method to obtain nanospheres with a particle size of less than 1 μm. The preparation method of this product is complicated and needs to be used with an additional binder. In addition, the product has poor anti-swelling ability, which may cause a decrease in adhesion during the cyclic charge and discharge process, reducing the battery life. It is not suitable for power batteries and fast charging directions, and small-particle products are not conducive to improving the injection speed, affecting production efficiency.

[0005] CN 113416270 A discloses a polymer and its preparation method and application. The polymer is prepared by using monomer A, monomer B and monomer C. The polymer is coated on the surface of the battery separator, which can significantly improve the thermal stability of the battery separator. However, the polymer microsphere is a linear polymer, which has poor electrolyte tolerance and is easily dissolved during use, and cannot effectively play a bonding role.

[0006] Therefore, it is necessary to develop a new polymer microsphere with a simple preparation method and easy to use, which can improve wettability while maintaining high swelling resistance. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a method for preparing a diaphragm, in which low-density polymer microspheres are blended with inorganic powders to form a slurry. After coating, the polymer microspheres float on the surface of the diaphragm to form a protrusion structure, and after a secondary polymerization reaction, a diaphragm with high adhesion and swelling resistance is obtained.

[0008] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0009] The first object of the present invention is to provide a method for preparing a diaphragm, comprising the following steps:

[0010] (1) In a redox initiation system, polymer microspheres, inorganic powders, and solvents are uniformly mixed to obtain a slurry;

[0011] (2) coating the slurry on a base film, and subjecting the polymer microspheres to a secondary polymerization reaction to obtain a separator;

[0012] The density of the polymer microspheres is less than 1 g / cm 3 ;

[0013] The particle size of the polymer microspheres is 0.5-8 μm.

[0014] The second object of the present invention is to provide a separator prepared by the aforementioned preparation method.

[0015] The third object of the present invention is to provide application of the aforementioned separator in a lithium ion battery.

[0016] A fourth object of the present invention is to provide a lithium ion battery comprising a positive electrode, a negative electrode and a separator, wherein the separator is the aforementioned separator.

[0017] The beneficial effect of the present invention is that the present invention adopts a density less than 1g / cm 3The low-density polymer microspheres are used to prepare a slurry and coated on a base film to form a diaphragm. Under the action of buoyancy, the low-density polymer microspheres can rise to the surface of the diaphragm and form a protrusion structure on the surface of the diaphragm. The protrusion structure can more effectively bond the diaphragm and the electrode, that is, improve the adhesion between the diaphragm and the electrode. In addition, the low-density polymer microspheres can be used through a secondary polymerization reaction to make the prepared diaphragm have good electrolyte tolerance and anti-swelling properties, and will not dissolve during the cyclic charge and discharge process, so as to exert a long-lasting bonding effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The photos of the emulsions prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 1 (A) is a photograph of the emulsion prepared in Example 1, Figure 1 (B) is a photograph of the emulsion prepared in Comparative Example 1;

[0019] Figure 2 This is a SEM image of the diaphragm prepared in Comparative Example 1;

[0020] Figure 3 This is a SEM image of the diaphragm prepared in Example 1;

[0021] Figure 4 This is the SEM image of the polymer microspheres prepared in Example 1. DETAILED DESCRIPTION

[0022] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.

[0023] The present invention provides a method for preparing a diaphragm, comprising the following steps:

[0024] (1) In a redox initiation system, polymer microspheres, inorganic powders, and solvents are uniformly mixed to obtain a slurry;

[0025] (2) The slurry is coated on a base film, and the polymer microspheres undergo a secondary polymerization reaction to obtain a diaphragm.

[0026] The present invention uses low-density polymer microspheres to prepare a slurry and coats it on a base film to form a diaphragm. Under the action of buoyancy, the low-density polymer microspheres can rise to the surface of the diaphragm and form a convex structure on the surface of the diaphragm. The convex structure can more effectively bond the diaphragm and the pole piece, that is, improve the bonding force between the diaphragm and the pole piece. Since the solvent used in the present invention is water, in order to enable the polymer microspheres to float to the surface of the diaphragm, the density of the polymer microspheres is less than 1g / cm 3 For example, it can be 0.75g / cm 3 , 0.8g / cm 3, 0.85g / cm 3 , 0.9g / cm 3 Or any value in the range formed by any two of the above values.

[0027] Since the thickness of the current lithium-ion battery separator is 5 to 15 μm, in order to adapt to the thickness of the separator, under preferred conditions, the particle size of the polymer microspheres in the present invention is 0.5 to 8 μm, for example, it can be 1 μm, 2 μm, 3 μm, 5 μm, 8 μm or any value in the range composed of any two of the above values. When the particle size of the polymer microspheres is controlled within the above-mentioned specific range, it is possible to leave enough space between the polymer microspheres and the positive and negative electrodes to accommodate the electrolyte, and the bonding force between the electrodes can be guaranteed. If the particle size of the polymer microspheres is too large, the number of protruding structures on the surface of the separator under the same mass is reduced, the positive and negative electrodes cannot be effectively bonded, and the injection amount is increased, resulting in a decrease in the battery energy density. If the particle size of the polymer microspheres is too small, the gap between the separator and the electrode is too small, which may in turn lead to a decrease in the injection efficiency.

[0028] According to the present invention, the inorganic powder is selected from one or more of alumina and boehmite.

[0029] In the present invention, the low-density polymer microspheres are incompletely reacted polymer microspheres, and the polymer microspheres also contain some incompletely reacted monomers. By adding an initiator and performing a secondary reaction, the incompletely reacted monomers can continue to polymerize. The initiator in the redox system includes an oxidant and a reductant. Among them, the types of the oxidant can be known to those skilled in the art, including but not limited to one or more of persulfate, dibenzoyl peroxide, cyclohexanone peroxide, tert-butyl hydroperoxide, hydrogen peroxide, and methyl ethyl ketone peroxide; the reductant is selected from one or more of glucose, sodium sulfite, sodium bisulfite, cyclohexane salt, and divalent iron ions.

[0030] According to the present invention, if the content of polymer microspheres is too much, the heat resistance of the diaphragm will be deteriorated, and if the content of polymer microspheres is too little, the adhesion of the diaphragm will be reduced. The mass ratio of the polymer microspheres to the inorganic powder is 1: (1~200), preferably 1: (2~50), for example, it can be 1: 2, 1: 5, 1: 10, 1: 15, 1: 20, 1: 25, 1: 30, 1: 35, 1: 40, 1: 45, 1: 50, 1: 100, 1: 150, 1: 200 or any value in the range of any two of the above ratios.

[0031] In the present invention, the solvent for preparing the slurry is water or an organic solvent. In order to improve economic benefits and protect the environment, the solvent is preferably water. Furthermore, the solid content of the slurry is 1-40wt%, that is, the total content of the polymer microspheres and the inorganic powder in the slurry is 1-40wt%.

[0032] In the present invention, the base film may be known to those skilled in the art, including but not limited to one or more of polyethylene (PE) film, polypropylene (PP) film, polyimide (PI) film, polyester (PET) film, polyacrylonitrile (PAN) film, and cellulose film.

[0033] In the present invention, the reaction degree of the polymer microspheres can be increased by the secondary polymerization reaction, which is beneficial to reduce the swelling of the polymer microspheres during the cyclic charge and discharge process and improve the electrolyte tolerance and swelling resistance of the film. The present invention can carry out the secondary polymerization reaction by adding an initiator in step (1) and controlling the reaction temperature of step (2). Furthermore, the reaction temperature of the secondary polymerization reaction is 20-90°C. In the present invention, the rate of the secondary polymerization reaction is affected by the reaction temperature. The higher the reaction temperature, the faster the rate of the secondary polymerization reaction. The reaction temperature of all secondary polymerization reactions is preferably 60-90°C. At this temperature, the film can be dried while the secondary polymerization reaction is being carried out.

[0034] In the present invention, the degree of reaction is controlled by controlling the type of monomers and the reaction conditions in the polymerization reaction to prepare a polymer having a density of less than 1 g / cm 3 Specifically, the method for preparing the polymer microspheres comprises: preparing the polymer microspheres in a protective atmosphere by using a polymerization reaction system consisting of a methacrylate monomer, a second monomer, a catalyst, a stabilizer and a solvent.

[0035] In the present invention, the yield of low-density polymer microspheres can be controlled by controlling the type of monomer, the time and temperature of the polymerization reaction. Further, the second monomer is selected from one or more of styrene, acrylic acid, acrylamide, acrylate, acrylonitrile, vinyl acetate, vinyl alkyl ether, ethylene oxide, o-dimethylphenol, terephthalic acid, ethylene glycol, bisphenol A, phosgene, maleic anhydride, hexamethylenediamine, adipic acid, norbornene, caprolactam, melamine, dimethyldichlorosilane, 1,3-butadiene, isoprene, chloroprene, and divinylbenzene; the methacrylate monomer includes but is not limited to one or more of methyl methacrylate, ethyl methacrylate, butyl methacrylate, propynyl methacrylate, allyl methacrylate, hydroxypropyl methacrylate, hydrogenated silicone oil-modified polymethyl methacrylate allyl ester.

[0036] Furthermore, the types of the catalyst may be known to those skilled in the art, including but not limited to one or more of inorganic acids, organic acids, alkali metals, alkali metal hydroxides, alkali metal alkoxides, peroxides, azo compound initiators, radiation, ultraviolet light, microwaves, plasma, reducing agents, organic bases, strong acidic cation exchange resins, acidic clay, alcohols, amines, benzophenone, and Grignard reagents. Wherein, the inorganic acid includes but is not limited to one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, perchloric acid, chlorosulfonic acid, and fluorosulfonic acid; the organic acid includes but is not limited to one or more of trifluoromethanesulfonic acid, trichloroacetic acid, trifluoroacetic acid, and oxalic acid; the Lewis acid includes but is not limited to one or more of boron trifluoride, aluminum chloride, titanium tetrachloride, tin tetrachloride, zinc chloride, and antimony chloride; the initiator includes one or more of peroxide initiator, azo initiator, Ziegler-Natta initiator, and metallocene initiator; the peroxide initiator includes but is not limited to cumene hydroperoxide, tert-butyl hydroperoxide, diisopropyl peroxide, di-tert-butyl peroxide, dibenzoyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diisopropyl peroxydicarbonate The invention relates to one or more of ester, dicyclohexyl peroxydicarbonate, potassium persulfate, ammonium persulfate, hydrogen peroxide, and sodium persulfate; the azo initiator includes but is not limited to one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, azobisisobutyramidine hydrochloride, and azoisobutylcyanoformamide; the ray includes but is not limited to one or more of X-ray, γ ray, β ray, α ray, and neutron ray; the type of the reducing agent may be known to those skilled in the art, including but not limited to one or more of ferrous chloride, cuprous chloride, sodium sulfite, ascorbic acid, hydrazine hydrate, potassium sodium tartrate, and glucose; the type of the organic base may be known to those skilled in the art, including but not limited to one or more of tetramethylammonium hydroxide, sodium naphthalene, n-butyl lithium, tert-butyl lithium, and potassium amide.

[0037] Furthermore, the types of the stabilizer may be known to those skilled in the art, including but not limited to one or more of polyvinyl pyrrolidone, polyvinyl alcohol, sorbitan monooleate, carboxylates, sorbitan monooleate, alkyl sulfonates, whey protein, monoglycerol fatty acid glyceride, α-olefin sulfonates, alkylbenzene sulfonates, phosphate diester salts, sorbitol fatty acid esters, alkylphenol polyoxyethylene ethers, alkylamide betaines, alkyl carboxy betaines, pentaerythritol fatty acid esters, phosphate monoester salts, sucrose fatty acid esters, sulfobetaines, aluminum sol, silica sol, and magnesium sol.

[0038] Further, the solvent is water or an organic solvent. The organic solvent may be known to those skilled in the art, including but not limited to one or more of m-cresol, N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, methanol, ethanol, n-propanol, isopropanol, n-butanol, ethyl acetate, tetrahydrofuran, acetone, ether, butanone, cyclopentanone, dichloromethane, chloroform, petroleum ether, n-hexane, hexamethyldisiloxane, toluene, and xylene.

[0039] Furthermore, the reaction temperature of the polymerization reaction is 50-90° C., and the reaction time is 0.5-10 h.

[0040] The present invention provides a diaphragm prepared by the above-mentioned preparation method. The diaphragm comprises a diaphragm body and a protruding structure protruding from the diaphragm body, and the protruding structure is the above-mentioned polymer microsphere. Under preferred conditions, the height of the protruding structure is 20-80% of the diameter of the polymer microsphere.

[0041] The present invention provides application of the aforementioned diaphragm in a lithium ion battery.

[0042] The present invention also provides a lithium ion battery, comprising a positive electrode, a negative electrode and a separator, wherein the separator is the above-mentioned separator.

[0043] The present invention will be described in detail below through examples.

[0044] The bonding strength was tested using a Labthink BLD-200N electronic peeling tester. The test method was as follows: the diaphragm was bonded to the positive electrode, pressed at 80°C and 1.5 MPa for 1 min, and then cut into rectangles of 30 mm in width and 200 mm in length. The diaphragm and electrode were then stretched at a rate of 2 mm / min, and the peel strength of the diaphragm was determined based on the peeling force.

[0045] The particle size of polymer microspheres was tested using a laser particle size tester.

[0046] Wettability test: Take a rectangular composite film with a width of 30 mm and a length of 200 mm, immerse the lower 3 cm of the composite film in the electrolyte, and hang the composite film above it at the same height to ensure that the composite film is vertical. Record the height of the electrolyte solvent line after 5 minutes.

[0047] Swelling test: Take 2g of polymer microspheres and place them in a tin foil plate with an inner diameter of 5cm for self-leveling. Dry them at 80℃ to obtain a circular film, and record the mass as m1. Soak the circular film in electrolyte at 60℃ for 24h, wipe off the surface electrolyte, and record the mass as m2.

[0048] Swelling rate = (m2-m1) / m1×100%.

[0049] Thermal shrinkage test: First, the diaphragm is cut into discs with a diameter of 19 mm using a punch, and its initial area S0 is calculated. Then, the oven temperature is increased to 150°C, and the diaphragm disc sample is placed in the oven for 1 hour and then taken out. The diameter of the diaphragm after heat treatment is measured, and the corresponding area S1 is calculated.

[0050] Thermal shrinkage =

[0051] Example 1

[0052] (1) Preparation of polymer microspheres: 90 g of deionized water, 1 g of polyvinyl pyrrolidone (PVP), 6 g of methyl methacrylate, 4 g of isooctyl acrylate, 1 g of hydroxyethyl acrylate, 0.2 g of benzoyl peroxide, 0.1 g of allyl methacrylate and 0.1 g of ethyl acetoacetate were reacted at 70 °C and a stirring speed of 200 r / min for 3 h to obtain an emulsion system as shown in Figure 1 (A) is shown. Figure 1 (A) It can be seen that the density of the polymer microspheres floating on the upper layer of the emulsion is smaller than that of water, that is, less than 1g / cm 3 After centrifugation and washing, floating polymer microspheres with a particle size of 2 to 5 μm (the mass is recorded as m 上 ) and precipitated polymer microspheres with a particle size of 5 μm (the mass is recorded as m 下 ), the ratio of the two is m 上 / m 下 Denoted as η.

[0053] Figure 4 This is the SEM image of polymer microsphere A1. Figure 4 It can be seen that the average particle size of the floating polymer microspheres prepared in Example 1 is about 2-5 μm.

[0054] (2) Preparation of diaphragm: With water as solvent, take alumina and the floating polymer microspheres obtained in step (1) in a mass ratio of 4:1, add BM900 (purchased from Japan Zeon) accounting for 5% of the total mass of alumina and polymer microspheres, and add tert-butyl hydroperoxide accounting for 0.6% of the mass of polymer microspheres and 0.4% of glucose, mix well, and obtain a slurry with a solid content of 20%; the slurry is evenly coated on a PE base film by a diaphragm coating device, the coating thickness is 8 μm, and the diaphragm is dried at 80°C after standing at room temperature for 2 hours to obtain a diaphragm.

[0055] Figure 3 This is a SEM image of the diaphragm prepared in Example 1. Figure 3 It can be seen that the polymer microspheres in the diaphragm prepared in Example 1 protrude from the diaphragm body to form a protruding structure, which effectively plays a role in bonding the diaphragm and the pole piece, that is, improves the bonding force between the diaphragm and the pole piece.

[0056] Comparative Example 1

[0057] (1) Preparation of polymer microspheres: 90 g of deionized water, 1 g of PVP, 6 g of methyl methacrylate, 4 g of isooctyl acrylate, 1 g of hydroxyethyl acrylate, 0.2 g of benzoyl peroxide, 0.1 g of allyl methacrylate and 0.1 g of ethyl acetoacetate were reacted at 80 °C and 200 r / min for 8 h to obtain an emulsion system as shown in Figure 1 (B) Figure 1 (B) It can be seen that the polymer microspheres in the emulsion have settled (i.e., the density of the polymer microspheres is greater than that of water), and after filtration and washing, polymer microspheres with an average particle size of 5 μm are obtained.

[0058] (2) Preparation of diaphragm: Using water as solvent, take aluminum oxide and the polymer microspheres obtained in step (1) in a mass ratio of 4:1, mix them evenly, and obtain a slurry with a solid content of 20%; the slurry is evenly coated on a PE base film by a diaphragm coating device, with a coating thickness of 8 μm, and then left to stand at room temperature for 2 h and then dried at 80° C. to obtain a diaphragm.

[0059] Figure 2 This is a SEM image of the diaphragm prepared in Comparative Example 1. Figure 2 It can be seen that the protrusion structure formed by the polymer microspheres in the diaphragm prepared in Comparative Example 1 is not obvious, so its bonding effect on the diaphragm and the electrode is not strong.

[0060] Examples 2 to 7 and Comparative Examples 2 to 3

[0061] The method of Example 1 was followed, except that the reaction temperature and time for preparing the polymer microspheres in step (1) were adjusted, as shown in Table 1.

[0062] Table 1

[0063]

[0064] From Table 1 we can see that:

[0065] It can be seen from Examples 1 to 7 that when the reaction time is 3 h, as the reaction temperature increases, the η value first increases and then decreases. Since only floating polymer microspheres and alumina microspheres are used to prepare the diaphragm, the change in the η value has no obvious change on the wettability of the diaphragm and the bonding strength between the diaphragm and the electrode.

[0066] It can be seen from Examples 1, 8-11 and Comparative Examples 4-5 that when the reaction temperature is 70°C, as the reaction time increases, the η value first increases and then decreases. If the reaction time is too short, no polymer microspheres are generated; if the reaction time is too long, since the monomers react completely at this time, no non-floating polymer microspheres exist in the emulsion system; and there is no obvious change in the wettability of the diaphragm and between the diaphragm and the electrode.

[0067] It can be seen from Comparative Example 1 that when the reaction temperature is 80°C and the reaction time is 8h, no floating polymer microspheres are formed, only precipitated polymer microspheres are formed. When the diaphragm is prepared with precipitated polymer microspheres, the bonding strength between the diaphragm and the electrode is low, and the diaphragm has poor anti-swelling properties.

[0068] It can be seen from Comparative Examples 2 and 3 that if the reaction temperature is too low, polymer microspheres cannot be generated even if the reaction time is extended; if the reaction temperature is too high, implosion will occur and polymer microspheres cannot be obtained.

[0069] Examples 12 to 14 and Comparative Example 6

[0070] The method of Example 1 was followed, except that the amount of the initiator in step (2) was changed, and the ratio of tert-butyl hydroperoxide to glucose in the initiator was kept unchanged, as shown in Table 2.

[0071] Table 2

[0072]

[0073] From Table 2 we can see that:

[0074] As the amount of initiator increases, the swelling of the diaphragm first decreases, and then increases slightly when it exceeds 1%. The possible reasons are: the increase in the amount of initiator will lead to a higher degree of polymerization completion, thereby reducing the swelling rate, but excessive initiator will reduce the molecular weight, resulting in an increase in the swelling rate.

[0075] Since no initiator is added in Comparative Example 6, the polymer microspheres do not undergo secondary polymerization reaction, the polymerization completion degree is low and the average molecular weight is low, the swelling rate of the diaphragm is significantly increased, the cohesive force is reduced, and the bonding strength is significantly reduced.

[0076] Examples 15-16 and Comparative Examples 7-8

[0077] The method of Example 1 is followed, except that isooctyl acrylate is replaced with other types of monomers, as shown in Table 3.

[0078] Comparative Example 9

[0079] The method of Example 1 is followed, except that the monomer used to prepare the polymer microspheres is only methyl methacrylate, as follows:

[0080] (1) Preparation of polymer microspheres: 90 g of deionized water, 1 g of PVP, 11.2 g of methyl methacrylate and 0.2 g of benzoyl peroxide were reacted at 70 °C and a stirring speed of 200 r / min for 3 h. No floating microspheres were produced in the obtained emulsion system. The product was centrifuged and washed to obtain polymer microspheres.

[0081] (2) Preparation of diaphragm: Using water as solvent, take aluminum oxide and the polymer microspheres obtained in step (1) in a mass ratio of 4:1, and add 0.6% of tert-butyl hydroperoxide and 0.4% of glucose accounting for the mass of the polymer microspheres, mix well, and obtain a slurry with a solid content of 20%; the slurry is evenly coated on a PE base film by a diaphragm coating device, with a coating thickness of 8 μm, and then left to stand at room temperature for 2 h and then dried at 80°C to obtain a diaphragm.

[0082] Table 3

[0083]

[0084] From Table 3 we can see that:

[0085] As the carbon chain of the monomer increases, the proportion of the prepared suspended polymer microspheres increases. When the number of carbon atoms in the alkyl side chain increases to 8, the η value reaches 15.67. And as the number of carbon atoms in the alkyl side chain increases, but when the carbon chain length exceeds 8, the adhesion weakens, which is due to the decrease in the cohesive force of the polymer.

[0086] When only methyl methacrylate was used as the monomer in Comparative Example 9, the obtained polymer microspheres were basically in the lower layer after centrifugal washing. The possible reasons are: the polymerization reaction proceeded at a high level and the density of methyl methacrylate was relatively high.

[0087] Examples 17 to 19 and Comparative Examples 10 to 11

[0088] The method of Example 1 is followed, except that the usage ratio of methyl methacrylate (monomer A) to isooctyl acrylate (monomer B) is changed, as shown in Table 4.

[0089] Table 4

[0090]

[0091] It can be seen from Table 4 that when the content of isooctyl acrylate increases, the η value also increases, the bonding strength first increases and then decreases, and the highest bonding strength is 3.39 N / m; when the amount of isooctyl acrylate is lower than that of methyl methacrylate, the swelling rate of the diaphragm does not change significantly with the increase of the amount of isooctyl acrylate.

[0092] Examples 20-23 and Comparative Examples 12-13

[0093] The method of Example 1 was followed, except that the mass ratio of polymer microspheres to alumina in step (2) was changed, as shown in Table 5.

[0094] Table 5

[0095]

[0096] From Table 5 we can see that:

[0097] As the amount of polymer microspheres increases, the wettability increases and the bonding strength increases because the polymer microspheres are more compatible with the electrolyte than alumina; when the amount of polymer microspheres decreases, the wettability and bonding strength both weaken. When the ratio of alumina to polymer microspheres is lower than 4:1, the heat resistance of the diaphragm deteriorates due to the reduction of inorganic content; when the ratio of alumina to polymer microspheres is higher than 4:1, as the amount of polymer microspheres decreases, the bonding effect weakens and the heat resistance of the diaphragm deteriorates; when the amount of alumina is greater than 50:1, as the amount of alumina increases, the shrinkage rate of the diaphragm also gradually increases. The possible reason is that the amount of polymer in the diaphragm is too small, causing the alumina powder to slip as the diaphragm shrinks, thereby increasing the shrinkage rate of the diaphragm.

[0098] Examples 24-26 and Comparative Examples 13-14

[0099] The method of Example 1 is followed, except that the median particle size of the polymer microspheres is different, as shown in Table 6.

[0100] Table 6

[0101]

[0102] It can be seen from Table 6 that: when the median particle size is less than 5μm, the bonding strength first increases and then decreases; when the median particle size is less than 0.5μm, the polymer microspheres are too small and the area of ​​the action sites is small, resulting in a bonding strength lower than 2N / m; when the median particle size is greater than 8μm, the microspheres are large and the action sites are few, resulting in a bonding strength lower than 2N / m.

[0103] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a diaphragm, characterized in that: The preparation method comprises the following steps: In a redox initiation system, polymer microspheres, inorganic powders and solvents are uniformly mixed to obtain a slurry; The slurry is coated on a base film, and the polymer microspheres are subjected to a secondary polymerization reaction to obtain a diaphragm; The density of the polymer microspheres is less than 1 g / cm 3 ; The particle size of the polymer microspheres is 0.5-8 μm; The method for preparing the polymer microspheres comprises: preparing the polymer microspheres in a protective atmosphere by using a polymerization reaction system consisting of a methacrylate monomer, a second monomer, a catalyst, a stabilizer and a solvent; The polymer microspheres are incompletely reacted polymer microspheres, which also contain some incompletely reacted monomers. The secondary reaction in the redox initiation system can enable the incompletely reacted monomers to continue to polymerize.

2. The preparation method according to claim 1, characterized in that: The inorganic powder is selected from one or more of alumina and boehmite; The initiator in the redox system includes an oxidant and a reductant; The oxidant is selected from one or more of persulfate, dibenzoyl peroxide, cyclohexanone peroxide, tert-butyl hydroperoxide, hydrogen peroxide, and methyl ethyl ketone peroxide; The reducing agent is selected from one or more of glucose, sodium sulfite, sodium bisulfite, and divalent iron ions.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the polymer microspheres to the inorganic powder is 1: (1-200).

4. The preparation method according to claim 3, characterized in that: The mass ratio of the polymer microspheres to the inorganic powder is 1: (2~50).

5. The preparation method according to claim 1, characterized in that: The reaction temperature of the secondary polymerization reaction is 20-90°C.

6. The preparation method according to claim 1, characterized in that: The reaction temperature of the polymerization reaction is 50-90° C., and the reaction time is 0.5-10 h.

7. The preparation method according to claim 1, characterized in that: The second monomer is selected from one or more of styrene, acrylic acid, acrylamide, acrylic ester, acrylonitrile, vinyl acetate, vinyl alcohol, vinyl alkyl ether, ethylene oxide, o-xylphenol, terephthalic acid, ethylene glycol, bisphenol A, phosgene, maleic anhydride, hexamethylenediamine, adipic acid, norbornene, caprolactam, melamine, dimethyldichlorosilane, 1,3-butadiene, isoprene, chloroprene, and divinylbenzene; The catalyst is selected from one or more of inorganic acid, organic acid, alkali metal, alkali metal hydroxide, alkali metal alkoxide, peroxide, azo compound initiator, radiation, ultraviolet light, microwave, plasma, reducing agent, organic base, strong acid cation exchange resin, acid clay, alcohol, amine, benzophenone, and Grignard reagent; The stabilizer is selected from one or more of polyvinyl pyrrolidone, polyvinyl alcohol, sorbitan monooleate, carboxylates, sorbitan monooleate, alkyl sulfonates, whey protein, monoglycerol fatty acid glyceride, α-olefin sulfonates, alkylbenzene sulfonates, phosphate diester salts, sorbitol fatty acid esters, alkylphenol polyoxyethylene ethers, alkylamide betaines, alkyl carboxy betaines, pentaerythritol fatty acid esters, phosphate monoester salts, sucrose fatty acid esters, sulfobetaines, aluminum sol, silica sol, and magnesium sol.

8. A diaphragm prepared by the preparation method according to any one of claims 1 to 7.

9. The diaphragm according to claim 8, characterized in that: The diaphragm comprises a diaphragm body and a protruding structure protruding from the diaphragm body, wherein the protruding structure is the aforementioned polymer microsphere; The height of the protrusion structure is 20-80% of the diameter of the polymer microsphere.

10. Use of the separator according to claim 9 in lithium ion batteries.

11. A lithium ion battery comprising a positive electrode, a negative electrode and a separator, characterized in that: The diaphragm is the diaphragm according to claim 9.

Citation Information

Patent Citations

  • Slurry for secondary battery porous membrane, secondary battery porous membrane, secondary battery electrode, secondary battery separator, and secondary battery

    CN103250273A

  • Polymer as well as preparation method and application thereof

    CN113416270A

  • Polymer microsphere, glued diaphragm suitable for cold pressing adhesion and preparation method of glued diaphragm

    CN118530416A

  • Laminated porous membrane, process for manufacturing same and separator for battery

    WO2014175050A1